Análise da distinção de adjunto adnominal preposicionado e complemento nominal de substantivo: uma perspectiva cognitiva - Anya Karina Campos D'almeida e Pinho (2017)
This research aims at investigating the existence of cognitive motivations for distinguishing prepositional noun adjuncts (NAs) from noun complements (CNs). Such investigation will look into the criteria used in Prescriptive Grammars (PG) to distinguish the two terms, as well as the criteria found in Descriptive Grammars (DG) to consider both terms, indistinctively, as post-modifiers of nouns. Upon examination of the criteria proposed in PGs and DGs regarding CN and NA, it is possible to reach the following generalizations: a) both CN and NA may be connected to nouns that indicate action and, when this occurs, the term in question is CN when it is the receiver of the action expressed by the noun (mentally transformed in verb for such checking) and NA when it is the agent of such action; b) CNs dont bind to concrete nouns; c) all phrases in the form de + X (in which X may be any term, including a clause) connected to a noun, are post-modifiers of that noun. Using Frame Semantics, by Fillmore, and Conceptual Blending Theory, by Fauconnier and Turner, this paper verifies the validity of these three affirmations by analyzing the blending type of nouns (concrete and action indicators) and nominal or adjectival terms, when linked by the preposition de. So far, the similarity of the blending in all cases indicates that there is no cognitive motivation to classify CNs and NAs as two distinct groups of clause elements.